Equity valuation of Millennium BCP - Zeller, Miguel Peixoto van (2018)
One of the most difficult tasks in the financial industry is to correctly access the fair value of a stock. In theory, the price of a stock should converge to its fair value over time, however the real fair value and the speed in which it will convert is what makes the stock price so difficult to predict. In order to perform a precise valuation, one should understand the intrinsics of the business and perform a variety of valuation methods in order to access the fair value. In this dissertation, I will analyze Millennium BCP, the major private bank in Portugal, stock price using mainly 2 methods: Dividend Discount Model and Multiples Valuation. These 2 methods combined resulted in a BUY recommendation, with an estimated fair price of €0.41 per share. In the end of the dissertation, I also compared my recommendation with JP Morgan Investment Bank report, to access the differences between my valuation and the Investment Bank valuation increasing the robustness of the final results. From this comparison, resulted that although JP Morgan used a different valuation method, the bank and the thesis recommend to BUY the Millennium’ stock, since both are optimistic on the future of the bank and the overall Portuguese banking system.